Hubungan Pengetahuan dengan Sikap Remaja Putri dalam Menghadapi Nyeri Haid (Dysmenorhea) di SDI Alakbar Bangsal Mojokerto - Farida Yuliani (Journal of Ners and Midwifery, 2017)
Dysmenorea is menstrual pain that the girly teenagers often feel. In Indonesia, the number of primarydysmenorea happen in 54,89% and the others are the type of patients facing menstrual pain. The kind of this study is analytic. The independent variable is knowledge and the dependent is the manner. The population counts 35 students. Taking samples is done by total sampling. The data taken are observed and analyzed by Chi Square. The result of this study shows us that having good knowledge counts 51% and the most respondent have positive manner in facing menstrual pain. Statical test using Chi Square test gets the result sig (2 talled)(0,026), so H1 will be accepted, if sig (2-tailed) <Î± so, based on Chi Square test shows us that H1 is acceptable, it means the relationship between knowlwdge and the manner of girly teenagers in facing menstrual pain. We hope the health workers more actively giving education about menstrual pain.